Nobat (Jabatan Muzium dan Antikuiti, 2001)
Documentary on Nobat, a special ceremonial music to accompany official court functions only to be played by royal command. The orchestra is made up of drums, flute,trumpet, and gong performed by a group of royal musicians from the same clan or family.The musical instruments are treated with the greatest respect. Principal occasions which call for Nobat accompaniment are at the coronation of a ruler, his funeral, or marriage